2018
DOI: 10.30845/jesp.v5n3p13
|View full text |Cite
|
Sign up to set email alerts
|

Adult Education Using the Moodle E-Learning Platform: The Role of the Trainer

Abstract: Distance learning is characterized by the use of technological tools that substitute for the physical presence of either the trainer or trainee and is also widely used in the field of adult education. The main feature of distance learning programs is the use of an asynchronous platform system (Moodle), which promotes learner's critical thinking and creativity by linking learning to practice, reflection, case study and exploration. The trainer, for his part, designs e-courses with the capabilities of using educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Bremer & Bryant [4] stated that 80% of students preferred Moodle vs Blackboard, being easier to use and having more tools that facilitate communication and collaboration. Pavlakou & Kalachanis [17] presented the main Moodle strengths and its efficiency in adult learning (life-long learning).…”
Section: Related Workmentioning
confidence: 99%
“…Bremer & Bryant [4] stated that 80% of students preferred Moodle vs Blackboard, being easier to use and having more tools that facilitate communication and collaboration. Pavlakou & Kalachanis [17] presented the main Moodle strengths and its efficiency in adult learning (life-long learning).…”
Section: Related Workmentioning
confidence: 99%
“…Distance learning has been proved to be a great success in adult education, as it provides sophisticated tools and supervisory training tools such as online learning platforms (Pavlakou & Kalachanis, 2018). Distance Learning takes place using asynchronous tele-learning systems, commonly known as "platforms", and includes a variety of course management tools, access tools to educational material resources, and synchronous and asynchronous communication tools.…”
Section: E Learning Transformative Learning and The Role Of The Trainermentioning
confidence: 99%
“…This means that the use of distance learning in adult education is fully in line with the principles of TL, as it includes the following parameters (Pavlakou & Kalachanis, 2018):…”
Section: E Learning Transformative Learning and The Role Of The Trainermentioning
confidence: 99%
“…We know that countries have been trying to improve and expand their distance learning services since the start of COVID‐19. Lastly, Pavlakou and Kalachanis (2018) found that the utilization of an electronic platform encourages each learner's unique learning path as well as participants' interactivity and ideas that are consistent with the critical thinking that underpins adult education principles. Furthermore, there are other studies exploring the effectiveness of multilingual and multicultural electronic platforms.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, the epistemological foundation and practices of adult education have been discussed and enriched by universities, ministries of education like the Turkish MoNE's General Directorate of Lifelong Learning, supranational organizations such as the European Union (EPALE, 2022), and international organizations such as UNESCO (2022). When delving deeper into the literature to cast light upon the practical initiatives focusing on contribution to adult education, what stands out is that there is a bulk of initiatives (i.e., Dokubo & Wami, 2020; Jameson et al, 2006; Pavlakou & Kalachanis, 2018) focusing on developing an interactive network with events, portals in which good experiences can be shared, and software applications for adult learning, to wit: EPALE (Electronic Platform for Adult Learning in Europe). In this respect, it seems that the EPALE can be the most comprehensive, multilingual, multinational, and effective one.…”
Section: Introductionmentioning
confidence: 99%